Expanded Human Blood-Derived γδT Cells Display Potent Antigen-Presentation Functions - Khan, Mohd Wajid A.; Curbishley, Stuart M.; Chen, Hung-Chang; Thomas, Andrew D.; Pircher, Hanspeter; Mavilio, Domenico; Steven, Neil M.; Eberl, Matthias; Moser, Bernhard (Frontiers in Immunology, 2014)
Cell-based immunotherapy strategies target tumors directly (via cytolytic effector cells) or aim at mobilizing endogenous anti-tumor immunity. The latter approach includes dendritic cells (DC), most frequently in the form of in vitro cultured peripheral blood monocytes-derived DC. Human blood γδT cells are selective for a single class of non-peptide agonists (“phosphoantigens”) and develop into potent antigen-presenting cells (APC), termed γδT-APC, within 1-3 days of in vitro culture. Availability of large numbers of γδT-APC would be advantageous for use as a novel cellular vaccine. We here report optimal γδT cell expansion (>107 cells/ml blood) when peripheral blood mononuclear cells (PBMC) from healthy individuals and melanoma patients were stimulated with zoledronate and then cultured for 14 days in the presence of IL-2 and IL-15, yielding γδT cell cultures of variable purity (77±21% and 56±26%, respectively). They resembled effector-memory &#945&#946T (TEM) cells and retained full functionality as assessed by in vitro tumor cell killing as well as secretion of proinflammatory cytokines (IFNγ, TNF&#945) and cell proliferation in response to stimulation with phosphoantigens. Importantly, day 14 γδT cells expressed numerous APC-related cell surface markers and, in agreement, displayed potent in vitro APC functions. Day 14 γδT cells from PBMC of patients with cancer were equally effective as their counterparts derived from blood of healthy individuals and triggered potent CD8+ &#945&#946T cell responses following processing and cross-presentation of simple (influenza M1) and complex (tuberculin purified protein derivative) protein antigens. Of note, and in clear contrast to peripheral blood γδT cells, the ability of day 14 γδT cells to trigger antigen-specific &#945&#946T cell responses did not depend on re-stimulation. We conclude that day 14 γδT cell cultures provide a convenient source of autologous APC for use in immunotherapy of patients with various cancers